The Effect of The Summarising Task Technique as A Strategy in Identifying Short Story Elements - Azaky, Andri; Elmustian, Elmustian; Charlina, Charlina (Journal of Educational Sciences, 2025)
Language skills are divided into receptive skills, i.e. listening and reading, and productive skills, i.e. speaking and writing. This study aims to overcome students' low interest in reading, which results in limitations in identifying the intrinsic elements of short story texts. The factors that cause this are a less supportive learning environment, teacher-centred learning methods and limited access to interesting reading materials. Using a quantitative experimental method, this research applied a one-group pretest-posttest design on students of Class XI B Madrasah Aliyah Imam Ibnu Katsir. An innovative strategy in the form of a summarising task technique was used as a learning treatment to produce post-test scores. The results showed a 50% increase in students' comprehension, with an average pre-test score of 4.3 increasing to 7.3 on the post-test, which was classified as moderate based on N-gain analysis. This strategy proved effective in improving students' ability to identify the essential elements of short story texts. The recommendations for other researchers can further develop technology-enhanced learning strategies. The aim is to increase student engagement, as well as long-term research to more fully evaluate the effectiveness of this method.